[Diagnostic (STARD) and prognostic (REMARK) studies]. - Altman, D; Bossuyt, P (2005)
Deficiencies in how research studies are reported are both well-documented and widespread across all medical specialties and study designs. Although randomised trials have received the most attention in this regard, similar concerns have been expressed about reporting of other types of research including diagnostic and epidemiological studies. If a journal article describes in enough detail what was done at each stage of a study, readers will have enough information to allow them to decide on the merits of the results for themselves. From this simple idea comes the scientific rationale of developing guidelines on how to report research. Recommended processes to produce reporting guidelines have evolved over several years during the preparation of a sequence of reporting guidelines starting with CONSORT and QUOROM in the 1990s. We describe initiatives to develop reporting guidelines for diagnostic accuracy studies (STARD) and tumour marker prognostic studies (REMARK).